2022
DOI: 10.1177/08948453221120961
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Decent Work Scale Measurement Model in Zimbabwe

Abstract: The Decent Work Agenda recognises the role of work and work-related contexts in giving meaning, fulfilment, opportunities for development and growth to the employed and those who aspire to work. The Decent Work Scale (DWS) is a commonly referenced measure to appreciate the experience of decent work in organizations. Limited research has examined the quality of the DWS measurement model in the developing countries, especially in sub-Saharan Africa. This study examined the factor structure of the DWS using bifac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The study also examined the measurement invariance (also known as measurement equivalence) of the IBI between gender groups. Measurement invariance evaluates whether the innovative work behaviour construct, measured using the IBI, is assessed the same way between gender groups (Sanhokwe & Takawira, 2022). Gender differences have been reported or critiqued in extant literature (see De Bruin & Steyn, 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…The study also examined the measurement invariance (also known as measurement equivalence) of the IBI between gender groups. Measurement invariance evaluates whether the innovative work behaviour construct, measured using the IBI, is assessed the same way between gender groups (Sanhokwe & Takawira, 2022). Gender differences have been reported or critiqued in extant literature (see De Bruin & Steyn, 2020).…”
Section: The Present Studymentioning
confidence: 99%
“…Even though DW research has been evolving for more than 20 years, there is a still lack of studies addressing the micro-level (Yan et al, 2023;Zammitti et al, 2021). Previous studies focused on the impact of organizational slack on innovative work behavior across managers and employees (Hügel and Kreutzer, 2020), while Sanhokwe and Takawira (2023) examined the impact of DW on IWB with the mediating role of organizational learning and work engagement in firms. Furthermore, Xu et al (2022) examined the relationship between decent work and innovative work behavior with the mediating role of intrinsic rewards, self-efficacy, and work engagement in a large stateowned holding company in Beijing.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, a bifactor model enables researchers to identify the variance common in a subscale that is not explained by a general factor (Dunn & McCray, 2020); is particularly valuable for evaluating the plausibility of the subscales and can lead to greater conceptual clarity (Dunn & McCray, 2020) of decent work, as Duffy et al (2020) suggested some potential nuances in measuring decent work in various countries, especially in non-western contexts. Unfortunately, only a few decent work studies have employed samples from sub-Saharan Africa (Atitsogbe et al, 2021; Sanhokwe & Takawira, 2022). Yet, decent work is highly relevant to the African continent, particularly in South Africa, where the problem of unemployment constitutes an ongoing difficulty (Nel, 2022).…”
Section: Introductionmentioning
confidence: 99%